Evidence of monotropic hexatic tilted smectic phase in the phase sequence of ferroelectric liquid crystal. (1st February 2018) - Różycka, Anna; Deptuch, Aleksandra; Jaworska-Gołąb, Teresa; Węgłowska, Dorota; Marzec, Monika
ABSTRACT: Physical properties of a new ferroelectric liquid crystal have been studied by complementary methods: differential scanning calorimetry, polarizing optical microscopy, dielectric and X-ray diffraction. It was found that next to enantiotropic ferroelectric smectic C* phase, the monotropic smectic phase appears at cooling. X-ray diffraction measurements allowed to identify this phase as hexatic tilted smectic. Temperature dependence of spontaneous polarization, tilt angle of molecules and switching time were found in both liquid crystalline phases at cooling. Based on the dielectric results, the dielectric processes were identified as Goldstone mode in the smectic C* phase, whereas as the bond-orientation-like phason and the bulk domain mode in the monotropic hexatic tilted smectic phase.